Sighting of Grey-Headed Lapwing Vanellus cinereus at Haripura Reservoir in Uttarakhand, India - Bhattacharjee, Anushree; Kidwai, Zaara (Journal of the Bombay Natural History Society (JBNHS), 2012)
No Abstract.